Congenital left hemidiaphragmatic agenesis : a case report - William Wijaya; Yustinus Rurie Wirawan (ARKA INSTITUTE, 2022)
Congenital diaphragmatic hernia is a congenital diaphragmatic disorder characterized by herniation of the abdominal viscera into the thoracic cavity. In rare diaphragmatic developmental abnormality cases, there is complete diaphragmatic agenesis. We report a case of left hemidiaphragmatic agenesis with usual postnatal course. A 13-day old female infant presented respiratory distress for a week. Chest radiograph showed left sided congenital diaphragmatic hernia. We report a left hemidiaphragmatic agenesis case. A 13-day old female infant presented respiratory distress for a week. Chest radiograph showed a left sided congenital diaphragmatic hernia. The patient undergo surgical exploration and was found to have an unusual and large defect in the left hemidiaphragm. No diaphragm is visible on the anterior and lateral sides, and the anterior sides presented only a small edge of the diaphragm. Agenesis of the left hemidiaphragm defect was identified and well managed by suturing the posterior edge of the diaphragm to the intercostal muscles. This report describes the well management of hemidiaphragmatic agenesis without incorporating a prosthetic material.